Nanovectorized Microalgal Extracts to Fight Candida albicans and Cutibacterium acnes Biofilms: Impact of Dual-Species Conditions - Virginie Lemoine; Clément Bernard; Charlotte Leman-Loubière; Barbara Clément-Larosière; Marion Girardot; Leslie Boudesocque-Delaye; Emilie Munnier; Christine Imbert (MDPI AG, 2020)
Biofilm-related infections are a matter of concern especially because of the poor susceptibility of microorganisms to conventional antimicrobial agents. Innovative approaches are needed. The antibiofilm activity of extracts of cyanobacteria Arthrospira platensis, rich in free fatty acids, as well as of extract-loaded copper alginate-based nanocarriers, were studied on single- and dual-species biofilms of Candida albicans and Cutibacterium acnes. Their ability to inhibit the biofilm formation and to eradicate 24 h old biofilms was investigated. Concentrations of each species were evaluated using flow cytometry. Extracts prevented the growth of C. acnes single-species biofilms (inhibition > 75% at 0.2 mg/mL) but failed to inhibit preformed biofilms. Nanovectorised extracts reduced the growth of single-species C. albicans biofilms (inhibition > 43% at 0.2 mg/mL) while free extracts were weakly or not active. Nanovectorised extracts also inhibited preformed C. albicans biofilms by 55% to 77%, whereas the corresponding free extracts were not active. In conclusion, even if the studied nanocarrier systems displayed promising activity, especially against C. albicans, their efficacy against dual-species biofilms was limited. This study highlighted that working in such polymicrobial conditions can give a more objective view of the relevance of antibiofilm strategies by taking into account interspecies interactions that can offer additional protection to microbes.